INTENSITY OF OXIDATIVE STRESS DEVELOPMENT IN RAT MAJOR CEREBRAL HEMISPHERES UNDER COMBINED CONDITIONS OF SYSTEMIC INFLAMMATORY RESPONSE, CHANGES IN THE NORMAL LIGHT-DARK CYCLE, AND FLUOXETINE ADMINISTRATION - O.A. Volkova; V.O. Kostenko (Проблеми екології та медицини)
At present, the relevance of examining changes to the normal light-dark cycle is increasing, and the connection between the development of the systemic inflammatory response (SIR) and circadian rhythm disorders has been confirmed. The effects of antidepressants on the human body are also actively studied. The aim of this study was to investigate the effect of fluoxetine on oxidative stress in the rat cerebral hemispheres under conditions of acute desynchronosis (AD), systemic inflammatory response (SIR), and fluoxetine administration. Material and methods. The study was conducted on 44 white Wistar rats weighing 150-200 kg of various articles, divided into 3 groups: control (15), a combination of AD and SIR (14), and a combination of AD, SIR, and fluoxetine (15). To simulate AD, a normal "light-dark" cycle (12 hours of light, 12 hours of darkness) was formed for 3 weeks, and the next 3 days the "light-dark" phases were shifted back by 6 hours. SIR was reproduced via intraperitoneal injection of Salmonella typhi lipopolysaccharide in the first week of 0.4 μg/kg 3 times a week, and in the following seven weeks – once a week. Fluoxetine was administered intragastrically for 21 days at a dose of 10 mg/kg and dissolved in 0.5 ml of distilled water at room temperature. In 10% of the homogenate of the large hemispheres of the brain, the rate of production of superoxide anion radical (SAR), the content of products that react with thiobarbituric acid (TBA-reactants), their increase, and the activity of catalase and superoxide dismutase (SOD) were determined. Results. The administration of fluoxetine in combination with AD and SIR reduced the rate of basic SAR production by 35.4%, NADPH-induced production by 34%, increased NADH-induced production by 65%, decreased the concentration of TBA-reactants by 23.7% and their augmentation by 54.3%, increased the activity of SOD by 85.7% and catalase by 12.4% compared to the group of combination of SIR and AD. Conclusions. When fluoxetine is administered alongside AD and SIR, it results in reduced baseline and NADPH-induced SAR production, increased NADH-induced production, decreased accumulation of TBA-reactants, and enhanced antioxidant activity in the rat cerebral hemispheres.